Novel pathogenic variants of DNAH5 associated with clinical and genetic spectra of primary ciliary dyskinesia in an Arab population - Al-Mutairi, Dalal A.; Alsabah, Basel H.; Pennekamp, Petra; Omran, Heymut (Frontiers in Genetics, 2024)
Introduction: Primary ciliary dyskinesia (PCD) is caused by the dysfunction of motile cilia resulting in insufficient mucociliary clearance of the lungs. This study aimed to map novel PCD variants and determine their pathogenicity in PCD patients in Kuwait. Methods: Herein, we present five PCD individuals belonging to a cohort of 105 PCD individuals recruited from different hospitals in Kuwait. Genomic DNAs from the family members were analysed to screen for pathogenic PCD variants. Transmission electron microscopy (TEM) and immunofluorescence (IF) analyses were performed on the nasal biopsies to detect specific structural abnormalities within the ciliated cells. Results: Genetic screening and functional analyses confirmed that the five PCD individuals carried novel pathogenic variants of DNAH5 causing PCD in three Arabic families. Of these, one multiplex family with two affected individuals showed two novel homozygous missense variants in DNAH5 causing PCD with situs inversus; another multiplex family with two affected individuals showed two newly identified compound heterozygous variants in DNAH5 causing PCD with situs solitus. In addition, novel heterozygous variants were identified in a child with PCD and situs solitus from a singleton family with unrelated parents. TEM analysis demonstrated the lack of outer dynein arms (ODAs) in all analysed samples, and IF analysis confirmed the absence of the dynein arm component of DNAH5 from the ciliary axoneme. Conclusion: The newly identified pathogenic variants of DNAH5 are associated with PCD as well as variable pulmonary clinical manifestations in Arabic families.